For better or worse The impact of upward social comparison on self-evaluations. [article]. - Collins, Rebecca L.
Upward social comparison is generally regarded as ego deflating, yet people often compare themselves with those whose abilities and attributes are better than their own. Upward comparison provides useful information, which may partially account for this behavior. Furthermore, it is proposed that upward comparison only sometimes results in more negative self-evaluations; it can also be self-enhancing. A review of studies testing upward comparison effects on self-evaluations, self esteem, and affect is consistent with this conclusion. Thus, people may make upward comparisons in hopes of enhancing their self-assessment. It is concluded that upward comparison is not in conflict with the desire for positive self-regard and indeed serves it indirectly (through self-improvement) and sometimes directly (by enhancing the self). -- (from the author)